Analysis of Canadian wood pellets for the presence of living phytopathogenic fungi and pinewood nematode. (29th July 2018) - Callan, B. E.; Leal, I.; Islam, A.; Foord, B.
Abstract : Wood pellets from two port storage silos and four pellet plants (manufacturing facilities) in British Columbia and one pellet plant in Quebec and wood chips used for pellet production from British Columbia were cultured to identify the viable fungi that were present. Living fungal pathogens and decay fungi were cultured from the pre‐production chips, but the fungi isolated from finished pellets were not of phytosanitary concern. The absence of living pinewood nematode in all samples analysed was confirmed by real‐time reverse transcription PCR. Genomic DNA from the pinewood nematode was present in the pre‐pellet chip samples and also in the finished pellets from three of the collection sources.